Pattern recognition - Gibson, William (Berkley, 2011)
Cayce Pollard owes her living to her pathological sensitivity to logos. In London to consult for the world's coolest ad agency, she finds herself catapulted, via her addiction to a mysterious body of fragmentary film footage, uploaded to the Web by a shadowy auteur, into a global quest for this unknown 'garage Kubrick'.